1994
DOI: 10.1002/nur.4770170106
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal attachment: Influence of mother–daughter and husband–wife relationships

Abstract: Intergenerational attachment relationships between the pregnant woman and her mother, her husband, and her fetus were examined. Self-completed instruments were used to measure the attachment variables for a convenience sample of 115 middle-class mothers who attended urban prenatal classes. Results supported the hypothesis that mother-daughter and husband-wife attachment were correlated positively. Contrary to study predictions, maternal-fetal attachment scores were not related to mother-daughter and husband-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 28 publications
2
19
0
3
Order By: Relevance
“…Though not predicted in this study, the findings of gestational age and quickening as impacting attachment confirmed the significance of the two most frequently found variables in the literature review (Berryman & Windridge, 1996;Bloom, 1995;Cranley, 1981Cranley, , 1984Gaffney, 1986;Grace, 1989;Heidrich & Cranley, 1989;Kemp & Page, 1987;Koniak-Griffin, 1988;Leifer, 1977;LoBiondo-Wood 1985;Mercer et al, 1988;Vito, 1986;Wayland & Tate, 1993;Zachariah, 1994). Seeing physical changes and feeling the baby move had a strong impact on these young women.…”
Section: Other Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Though not predicted in this study, the findings of gestational age and quickening as impacting attachment confirmed the significance of the two most frequently found variables in the literature review (Berryman & Windridge, 1996;Bloom, 1995;Cranley, 1981Cranley, , 1984Gaffney, 1986;Grace, 1989;Heidrich & Cranley, 1989;Kemp & Page, 1987;Koniak-Griffin, 1988;Leifer, 1977;LoBiondo-Wood 1985;Mercer et al, 1988;Vito, 1986;Wayland & Tate, 1993;Zachariah, 1994). Seeing physical changes and feeling the baby move had a strong impact on these young women.…”
Section: Other Findingssupporting
confidence: 88%
“…While gestational age and quickening were the two most frequently found factors enhancing attachment, other variables such as social support, self-esteem, anxiety, stress, demographics, and risk status were inconsistent (Ard, 2000;Berryman & Windridge, 1996;Bloom, 1995;Colpin, De Munter, Nys, & Vandemeulebroecke, 1998;Condon, 1993;Cranley, 1981Cranley, , 1984Damato, 1998;Gaffney, 1986;Gau, 1996;Grace, 1989;Heidrich & Cranley, 1989;Hinz, 1997;Huth-Bocks, Levendosky, Theran, & Bogat, 2004;James, 1997;Kemp & Page, 1987;Koniak-Griffin, 1988;Leifer, 1977Leifer, , 1980Litt, 1996;LoBiondo-Wood, 1985;Mathews, 1999;Mercer, Ferketich, May, De Joseph, & Sollid, 1988;St. John, 2002;Shieh, 1998;Siddiqui & Hagglof, 1999;Tyler, 1992;Vito, 1986;Wayland & Tate, 1993;Wilson, 1990;Zachariah, 1994).…”
mentioning
confidence: 98%
“…The items are scored on a 5-point Likert-scale (05definitely no to 55definitely yes). One item, 'I feel my body is ugly', which has a reversed scoring, is sometimes deleted because it is not indicative of maternal feelings (Grace, 1989;Muller & Ferketich, 1993;Zachariah, 1994). Furthermore, since Sjö gren et al (2004) used the MFAS from early pregnancy onwards they removed seven items that can only be answered after quickening is felt; they also used a fourchoice format instead of a five-choice format.…”
Section: Maternal Foetal Attachment Scale (Mfas)mentioning
confidence: 96%
“…For all MFR scales reviewed, significant relationships were not always found for many specific pregnancy-related factors (such as gestational age, parity, gravidity, planning of the pregnancy, infertility history, knowing the gender of the baby, medical intervention during pregnancy, having twins) as well as for most of the demographic variables (such as age of the mother, educational level, socio-economic status, ethnicity, marital status, duration of the partner relationship and martial satisfaction) (MFAS: Ahern & Ruland, 2003;Bloom, 1995;Cranley, 1981;Curry, 1987;Grace, 1989;Heidrich & Cranley, 1989;Hjelmstedt et al, 2006;Huang et al, 2004 [Modified]; Kemp et al, 1990;Koniak-Griffin, 1988;Lindgren, 2001;Mercer et al, 1988;Muller, 1993Muller, , 1996Shieh & Kravitz, 2006;Sjö gren et al, 2004;Van den Bergh, 1989;Wilson et al, 2000;Zachariah 1994; MAAS: Condon, 1985;Condon & Corkindale, 1997;Condon & Esuvaranathan, 1999;Feldman, 2007;Hart & McMahon, 2006;Tsartsara & Johnson, 2006;PAI: Armstrong, 2002;Damato, 2000;Hjelmstedt et al, 2006;Lawson & Turriff-Jonasson, 2006;Muller, 1993;Prenatal Tool: Kemp & Page, 1987).…”
Section: Specific Pregnancy-related Factors and Demographic Factorsmentioning
confidence: 99%
“…Studies have shown that prenatal parental attachment increases as the pregnancy progresses (Wu and Eichmann, 1988;Grace, 1989;Zachariah, 1994). Moreover, it has been revealed that prenatal attachment predicts postnatal maternal role attainment (Fowles, 1996), maternal attachment behaviour (Gloger-Tippelt, 1991) and the child's attachment (Benoit et al, 1997).…”
mentioning
confidence: 97%